Bandwidth Prediction in Zoom Meetings: A Mathematical Model Based on Feature Configuration Analysis - Andi Cahyono; Muhammad Taufiq Nuruzzaman; Bambang Sugiantoro; Sumarsono Sumarsono (Informatika, Universitas Jenderal Soedirman, 2026)
Video conferencing applications such as Zoom Meeting require sufficient and stable bandwidth to maintain communication quality. However, bandwidth needs often vary depending on user configurations, including video resolution, audio bitrate, and content-sharing activity. This study aims to develop a mathematical formula capable of accurately estimating bandwidth requirements for Zoom Meeting sessions. The methodology combines quantitative experiments and numerical simulations by collecting throughput data using Wireshark, analysing feature-based parameter variations, and validating the proposed formula through MATLAB simulation. Data were obtained from multiple Zoom sessions executed under controlled conditions with different feature combinations and replicated twenty times to ensure accuracy. The validation results show that the formula consistently provides realistic and stable estimations when compared with actual throughput measurements and simulation outcomes. The proposed model offers a simple yet effective tool for predicting bandwidth requirements, supporting efficient network capacity planning, and enhancing the overall performance of video conferencing environments.